2020
DOI: 10.1002/slct.202001566
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase‐Mimetic and Fenton‐Like Activities of Molybdenum Oxide Quantum Dots

Abstract: Molybdenum oxide nanomaterials have become a popular nanomaterial while its catalysis behavior especially the bio‐catalysis property is little understood, even though molybdenum has been employed as a key cofactor in several important enzymes in biological system. On the basis of these, the Fenton and peroxidase‐like property of molybdenum oxide quantum dots (MoOx QDs) with mixed valence state was carefully investigated using tetramethylbenzidine (TMB) and methyl orange (MO) as the substrates. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Compared with natural enzymes, nanozymes possess prominent advantages of controllable activity, high stability, good durability, and low cost, which have been widely used in the fields involving biomedicine, environment, and industry. Recently, nanozyme antibacterial therapy (NABT) has been established with broad-spectrum antibacterial activity against miscellaneous bacteria and even MDR bacteria. NABT commonly employs peroxidase-like nanozymes, which can decompose hydrogen peroxide (H 2 O 2 ) into deleterious reactive oxygen species (ROS) for bacterial elimination. Nevertheless, the low catalytic activity of nanozymes largely limits their antibacterial efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with natural enzymes, nanozymes possess prominent advantages of controllable activity, high stability, good durability, and low cost, which have been widely used in the fields involving biomedicine, environment, and industry. Recently, nanozyme antibacterial therapy (NABT) has been established with broad-spectrum antibacterial activity against miscellaneous bacteria and even MDR bacteria. NABT commonly employs peroxidase-like nanozymes, which can decompose hydrogen peroxide (H 2 O 2 ) into deleterious reactive oxygen species (ROS) for bacterial elimination. Nevertheless, the low catalytic activity of nanozymes largely limits their antibacterial efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…[337,338] Nanozymes possess fascinating enzymatic catalytic properties, which show many advantages (e.g., low-cost, excellent durability, high stability, and tunable catalytic activity) over natural enzymes, and have been widely used in many fields such as biomedicine, industry, environment and so on. [339][340][341][342][343] In recent years, GDY-based nanozymes for antibacterial therapy has been regarded as an effective alternative approach with remarkably enhanced antibacterial efficacy in a broadband spectral region, [29,38,73,137,344,345] compared with traditional nanozymes (e.g., Cu 2 WS 4 NCs, [346,347] MoO x QDs, [348,349] ) due to the highly 𝜋-conjugated hexagonal pore, [12,33] good photostability, [350] tunable E g , [20] and high charge carrier mobility. [20] For example, in 2022, Zhang et al [344] reported on B-GDY that could largely simulate the production of peroxidase, and the bactericidal activity against both Gram-positive and Gram-negative bacteria was largely boosted due to the highly catalytic activity of B-GDY, in good agreement with the theoretical prediction that the doping of B atoms could provide abundant active B-defect sites and significantly lowered G in the process of H 2 O 2 decomposition.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Over the past decade, various methods have been adopted to synthesize two-dimensional inorganic derivatives such as graphene [ 80 ], phosphorene [ 81 ], 2D layered carbides-based QDs [ 82 ], and TMOs-based QDs [ 83 ]. Due to the similar layer structures (the strong covalent or ionic bonds in layers, the weak van der Waals forces in interlayers), the synthesis of 2D MXene-derived QDs is quite similar to other inorganic QDs.…”
Section: Preparation Of Mqdsmentioning
confidence: 99%